DESIGN AND REALIZATION OF A DRYER SYSTEM WITH THE ADDITION OF A BLOWER - Abdul Haris Salam; Teuku Rihayat; S Sariadi; Awanis Ilmi; Rika Annisa; L Lianti; R Rusydi (Jurnal Sains dan Teknologi Reaksi, 2023)
Drying Blower Oven technology by testing the feasibility to be seen with tests such as nutrient content test, ash content test, water content test, organoleptic test to marketing test. Testing of the Drying Blower Oven is carried out by testing the raw material of the product, such as red chili. Drying using Drying Blower Oven at a temperature of 32.2ËšC to 54.2ËšC with a wind speed of 12 m/s until the water content is below 8% - 10%. This study aims to determine the drying characteristics of red chili with Multioven Cabinet Type changes in temperature, relative humidity, material weight loss, air flow rate, air volume rate, material moisture content against time, drying rate against time, and drying rate against moisture content. This study uses a descriptive method of drying temperature used below 65ËšC repeated 3 (three) times until it reaches a moisture content of 8-10 %wk. The results of the observations showed that the drying process recorded Rh outside the drying apparatus between 83.28%-89.50%. Also the Rh in the Drying apparatus was observed and was observed to be between 86.58%-97.91%. The red chili content during the drying process decreased from 38.75% down to an average of 18.05% with details in rooms one and two reaching 17.4%, rooms three and four 16.95% and spaces five and six 16, 6%. With an observation time of 4 hours.Keywords: Drying Blower Oven, Technology, Instant Seasoning